Computational physiological modeling for lung-specific ventilation and perfusion management in ex vivo lung perfusion - Imholz, Daan; Braithwaite, Sue A.; Blankman, Paul; Oppersma, Eline; de Jongh, Frans H. C.; de Heer, Linda M.; Luijk, Bart; Buhre, Wolfgang F. F. A.; Donker, Dirk W.; van Loon, Lex M. (Frontiers in Physiology, 2026)
IntroductionEx vivo lung perfusion (EVLP) relies on standardized ventilation and perfusion protocols to evaluate and preserve donor lungs before transplantation. Yet, these protocols overlook graft-specific physiology, leading to variable dead-space ventilation, intrapulmonary shunting, and increased lung injury.MethodsWe developed and validated a computational physiological model (CPM) of lungs on EVLP. The CPM integrates established principles of lung mechanics, gas exchange, and perfusion with clinical input data. It provides mechanistic insight into ex vivo lung physiology and quantifies intrinsic properties such as alveolar dead space and intrapulmonary shunting. Model validation combined in silico experiments to verify physiological coherence with calibration against clinical EVLP data to evaluate predictive performance.ResultsSimulation results closely aligned with clinical measurements of left atrial partial oxygen pressure (root mean squared error (RMSE) of 6.4 mmHg). Sensitivity analysis and uncertainty quantification further elucidated key determinants of oxygen and carbon dioxide dynamics, including the inspired oxygen fraction, intrapulmonary shunt, dead space, and perfusate flow.DiscussionThis CPM enhances understanding of ex vivo lung physiology, which may lead to less injurious EVLP management and support safe, extended-duration EVLP.